Exploration and Effectiveness Test from Some Tea Indigenous Potassium Soluble Bacteria - Pranoto, Eko; Wulansari, Restu; Athallah, Faris Nur Fauzi; Lestari, Fitrianti Widya (Research Institute for Tea and Cinchona, 2016)
Tea is a plant that benefits for health. The growth of tea plant was influenced by several factors, including superior clones and nutrient availability in soil. One of the most important macro nutrients is potassium. However, the availability of potassium is low because of retention on the soil. One of the methode for absorbed by plant was used Potassium Solubilizing Bacteria (PSB) with its organic acid function. The aim of the study was to explore and determine the density of colonies (DC) and the potential of Tea Indigenous PSB. Inoculum source from tea rhizosphere and rhizoplan of GMB 7, GMB 9 and TRI 2024 clones. The experimental design used was completely randomized design with six treatments and four replications, i.e. : GMB 7 Rhizosphere; GMB 7 Rhizoplan; GMB 9 Rhizosphere; GMB 9 Rhizoplan; TRI 2024 Rhizosphere; and TRI 2024 Rhizoplan. Ten isolates with the highest halozone was tested by the Dissolution Index (DI) of the PSB. The result showed that the highest DC was GMB 9 rhizoplan by 10.9 x 105 CFU/g and the lowest was TRI 2024 rhizoplant by 3.1 x 105 CFU/g. The DC on GMB clones series showed that rhizoplan was 14,29% higher than rhizosphere. There is no significant difference of DI for PSB colonies from all clones. From that clones, we were obtained 10 isolat that have the highest halozone, that were 2 isolates from rhizosphere and 8 isolates from rhizoplan. The average of DI rhizosphere isolates was 119,9% higher than rhizoplan.